PRODUCTIVITY ANALYSIS OF EXCAVATOR AND DUMP TRUCK HEAVY EQUIPMENT ON DIGGING AND LOADING WORKS FLOOD CONTROL AFVOER WATUDAKON MOJOKERTO - Rafi, Yudha Fatkur; Witjaksana, Budi (Jurnal Teknik Sipil, 2023)
Heavy equipment is a vital resource in a project, but renting heavy equipment is a costly undertaking. Besides that, a project always has constraints that allow the project completion time to exceed the specified time, and delays will also cause costs incurred to increase. So from the calculation of the productivity of heavy equipment, it is necessary so that the tool can work optimally. From the analysis results, it was found that the productivity of excavators was 154.185 m3/Hour. For dump trucks, it was 37.99 m3/Hour, then calculating the duration of work. For heavy equipment excavators, it took 454 Hours, and for dump trucks, it took 263 O'clock. For the cost of renting heavy equipment from the calculation of the analysis of the cost of renting heavy equipment for excavators, a value of Rp.1,985,200/Day is obtained, while for dump trucks, it is Rp.2,578,000/Day